HUBUNGAN PEMBELAJARAN BERMAKNA DAN STRATEGI METAKOGNITIF DENGAN PEMAHAMAN KONSEP IPAS SISWA KELAS III SDN BREBES 01 - Cahya Septiana, Wiwit; Didik Tri Setiyoko; Rila Melyana Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The results of the study showed that (1) meaningful learning has a significant relationship with the understanding of the concept of science, as evidenced by a significance value of 0.042 < 0.05 and a t-count value of 2.102 > t-table 2.026. (2) Metacognitive strategies have a significant relationship with the understanding of the concept of science, as evidenced by a significance value of 0.000 < 0.05 and a t-count value of -7.396. (3) Meaningful learning and metacognitive strategies simultaneously have a significant relationship with the understanding of the concept of science, as evidenced by a significance value of 0.000 < 0.05 and a F-count value of 38.675 > F-table 3.25. The coefficient of determination (R²) value of 0.676 indicates that meaningful learning and metacognitive strategies contribute 67.6% to the understanding of the concept of science, while the remaining 32.4% is influenced by other factors outside the study.